From career decision-making to career decision-management: New trends and prospects for career counseling - Argyropoulou, Katerina; Kaliris, Andronikos (Advances in Social Sciences Research Journal, 2018)
The primary goal of this paper is to present a number of recent major theoretical and empirical advances in the field of career decision-making since this process has been increasingly identified by experts as a relatively subjective experience. In this line, a series of conceptual shifts concerning career decision-making and the relevant fundamental problem of career indecision are described. In particular, it seems that the scope of career guidance and counseling has moved from some rigid constructs (e.g. “sources of indecision”, “decision-making styles”) to more flexible, dynamic, holistic and multi-dimensional concepts (e.g. “coping strategies”, “positive psychosocial strengths-resources”, “future time perspective”) that may support the individuals in making better career decisions in the complex world of work of the 21st century. Another aim of the article, on the basis of the aforementioned developments, is to provide proposals for the construction of an effective model for dealing with career decision-making challenges, in which the transition from the simple possession of related skills to the need of managing the decision-making process is adumbrated. Finally, specific implications and ideas regarding the use of methods and techniques intended for career interventions with young adults are discussed.